تأثيرنموذج فكر وزاوج وشارك في تنمية مهارة الكلام لدي طلاب المدرسة الثانوية الإسلامية - Suci Nur Anggraini; Mulyadi; Agung Yusup (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2026)
This study aims to determine the effect of the Cooperative Learning model, specifically the Think Pair Share (TPS) type, on students’ speaking skills (maharah al-kalam). This research used a quantitative approach with a quasi-experimental design, namely the pretest-posttest control group design. The sample consisted of two classes: an experimental class and a control class, with a total of 28 students. Data were collected through tests (pretest and posttest) and documentation. Data analysis included normality test, homogeneity test, and hypothesis testing using independent sample t-test. The results showed that the post-test mean score of the experimental class was higher than that of the control class. The hypothesis test result indicated a significance value of < 0.05, meaning that TPS had a significant effect on students’ speaking skills. TPS proved effective in improving students’ participation, confidence, and speaking fluency.